2017
DOI: 10.1007/s00425-017-2670-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol metabolism in differently colored cultivars of red currant (Ribes rubrum L.) through fruit ripening

Abstract: Rare red currants colors caused by low anthocyanin content in the pink and a lack of anthocyanins in the white cultivar correlated with low ANS gene expression, enzyme activity, and increased sugar/acid ratios. Changes in the contents of polyphenols, sugars, and organic acids in berries of the three differently colored Ribes rubrum L. cultivars ('Jonkheer van Tets', 'Pink Champagne', and 'Zitavia') were determined by LC-MS and HPLC at 4 sampling times during the last month of fruit ripening. The activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…have also received significant scrutiny from researchers. 18 , 19 These nonpigmented nongrape berries could be considered as candidates for the production of white berry wines and may thus contribute to the diversity of the berry wine market.…”
Section: Introductionmentioning
confidence: 99%
“…have also received significant scrutiny from researchers. 18 , 19 These nonpigmented nongrape berries could be considered as candidates for the production of white berry wines and may thus contribute to the diversity of the berry wine market.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the composition and content of anthocyanins and other polyphenols in fruits are the consequence of complex metabolic networks, regulated by genetic, developmental and environmental factors [ 7 11 ]. Flavonoids are synthesized via the phenylpropanoid/flavonoid pathway, the main steps of which are well known [ 4 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Slovenia, researchers found that the amount of polyphenol decreased in the last 3 weekss of ripening in red, pink, and white currant. Authors reported that the relative concentrations of hydroxycinnamic acids and flavonols increased in white and pink currants (Zorenc et al, 2017). Also in another studies recorded that phenolic acids decreased from 51.18 mg kg −1 (light-redd maturation) to 42.97 mg kg −1 (red maturation) in Rovada cultivar.…”
Section: Resultsmentioning
confidence: 92%